Soils : (Cambridge University Press, 2006)
This book was born as an international tribute to Fiorenzo C. Ugolini, an outstanding soil scientist, who recently retired from university teaching and research. It is a fully up-to-date synthesis of the present knowledge of soils, their genesis, functions and management. It includes contributions from leading soil scientists and the result is a book that provides the basic concepts as well as the latest data and